Comparison of the immersion chilling and freezing and traditional air freezing on the quality of beef during storage. Issue 12 (21st October 2021) - Ren, Wanyu; Yuan, Guoqiang; Lin, Xueer; Guo, Xiaohui; Wang, Zengli
Abstract: Compared to traditional air freezing, immersion chilling and freezing shows an improvement in the freezing effect on meat quality, but it is not known whether this advantage persists over longer storage periods. Therefore, the objective of the current study was to compare the effects of immersion chilling and freezing (ICF) and traditional air freezing (TAF) on the physical and chemical indexes in beef longissimus muscle during a storage period of 150 days. In the current study, the longissimus muscle from Luxi cattle (aged 20–24 months) was analyzed, with samples independently frozen by ICF and TAF. After the core temperature was frozen to below −18 degrees by the two chilling methods, samples were transferred to a −18 degrees cold room for further storage. During the storage period, physical and chemical indexes, mainly including color and texture qualities, total volatile base nitrogen (TVB‐N) and peroxide value (POV) were measured and comparatively analyzed at several fixed time points. A higher freezing rate was observed in ICF (5.124 cm/h) than in TAF (0.194 cm/h), and better microstructure was observed in ICF treatment. Besides, peak force values and total energy values were significantly lower in the TAF group than in the ICF group during the first 45 days of freezing storage time ( p < .05). ICF also showed better color quality due to higher L* values than TAF samples during the first 75 days of frozen storage ( p < .05). In addition, the thawing loss (after 75 days of storage), total volatile base nitrogen, and peroxide value (in the 30 to 75 days of storage period) were lower in the ICF than in the TAF group. In conclusion, the immersion chilling and freezing is more conducive to the quality of beef during storage at −18 degrees compared to traditional air freezing. Abstract : Freezing is one of the most effective ways to preserve the quality of beef and is used to minimize the product loss. Many studies have demonstrated that the immersion chilling and freezing shows good improvement on the freezing effect of meat quality; however, it is not known whether this advantage will still exist in a longer storage period. The aim of current study was to explore the effects of different freezing methods, including the immersion chilling and freezing (ICF) and traditional air freezing (TAF), on the physical and chemical indexes in beef longissimus muscle during a period of 150‐day storage.